Speech and language therapists’ approaches towards adults who stutter and its consequences on assessment and treatment - Uysal, Halil Tayyip; Incebay , Önal; Köse , Ayşen (Revista de Investigación en Logopedia, 2023)
Speech-Language Therapists (SLT) may have negative approaches toward Adults Who Stutter (AWS). There is no consensus about the SLT perspectives on AWS. This study aimed to investigate the SLT approach to AWS and assessment-therapy components in their practices. SLT (N=209) were included in the study. The survey consisted of four sections: demographic information, assessment-therapy components, and attitudes. The results are reported through boxplot graphics. The majority of the SLT were female (86.6%) and aged in the young group (20-29 years) (81.2%). SLT noted that they frequently used non-standard tools in the assessments and traditional or contemporary methods are preferred in the therapy components.  The participants mentioned that important to AWS's quality of life, resilience, and psychosocial characteristics. SLT are more likely to utilize non-standard approaches while evaluating AWS. Traditional methods, as well as current approaches, are preferred by the SLT. SLT cares about AWS's resilience and temperament differences.
Keywords: attitudes; speech-language therapists; stuttering; therapeutic alliance